2020
DOI: 10.1108/dlp-12-2019-0043
|View full text |Cite
|
Sign up to set email alerts
|

User-driven efforts in creating knowledge graph information system

Abstract: Purpose This paper presents the results of a qualitative study that involved students of an interdisciplinary PhD program. The study objective was to gather requirements to create a knowledge graph information system. The purpose of this study was to determine information-seeking practices and information needs of this community, to inform the functionalities of a proposed system, intended to help students with relevant resource discovery and decision-making. Design/methodology/approach The study design incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 28 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…This knowledge is often referred to as experiential or tacit knowledge, here operationalized as the values and quality of the resource of interest, as perceived by students [14]. Resources that help students discover appropriate faculty to collaborate with are especially critical for this population [3,4,10], as well as information about research topics of interest [3,7,11].…”
Section: Tacit Knowledge Exchange For Phd Studentsmentioning
confidence: 99%
See 4 more Smart Citations
“…This knowledge is often referred to as experiential or tacit knowledge, here operationalized as the values and quality of the resource of interest, as perceived by students [14]. Resources that help students discover appropriate faculty to collaborate with are especially critical for this population [3,4,10], as well as information about research topics of interest [3,7,11].…”
Section: Tacit Knowledge Exchange For Phd Studentsmentioning
confidence: 99%
“…Faculty profile pages can be a lightweight data source of potential connections between researchers and students from diverse fields, and community stakeholders [19], and can provide a way to identify one's place in the interdisciplinary community. However, in the case of the program studied here, students reported that faculty profiles are often not up to date, and too numerous to inspect thoroughly [10]. Also, expert finding applications in the scholarly domain are usually based on recommending acclaimed researchers based on their publication history [i.e.…”
Section: Network-based Representation and Discoverymentioning
confidence: 99%
See 3 more Smart Citations